2002
DOI: 10.1007/s11738-002-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sucrose accumulation and activities of sucrose-phosphatase, sucrose synthase, neutral invertase and soluble acid invertase in micropropagated sugarcane plants

Abstract: The activities of sucrose-phosphate synthase (SPS), sucrose synthase (SUSY), neutral invertase (NI) and soluble acid invertase (SAI) regulates sucrose activity in sugarcane were studied. Micropropagated sugarcane plants were obtained from callus cultures of four Mexican commercially available sugarcane varieties characterized by differences in sugar production, and activities of SPS, SUSY, NI, SAI and concentrations of sucrose were monitored in the sugarcane stem. The resuits indicated that sucrose accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
(25 reference statements)
5
20
0
Order By: Relevance
“…Data are mean ± SE with three biological replicates Planta (2011) 234:445-457 453 suggesting that the accumulated Pro is not a key factor for the observed greater tolerance of M. falcata to freezing. There have been numerous reports demonstrating that cold acclimation-induced increases in soluble sugars are positively correlated with freezing tolerance in a number of species (Castonguay et al 1995;Wanner and Junttila 1999;Gilmour et al 2000;Gutierrez-Miceli et al 2002;Klotke et al 2004). Our results demonstrated that soluble sugar and sucrose contents were significantly correlated with freezing tolerance in M. falcata, but not in M. truncatula (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Data are mean ± SE with three biological replicates Planta (2011) 234:445-457 453 suggesting that the accumulated Pro is not a key factor for the observed greater tolerance of M. falcata to freezing. There have been numerous reports demonstrating that cold acclimation-induced increases in soluble sugars are positively correlated with freezing tolerance in a number of species (Castonguay et al 1995;Wanner and Junttila 1999;Gilmour et al 2000;Gutierrez-Miceli et al 2002;Klotke et al 2004). Our results demonstrated that soluble sugar and sucrose contents were significantly correlated with freezing tolerance in M. falcata, but not in M. truncatula (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Exogenous supply of sugars enhances freezing tolerance in a number of species (Tabaei-Aghdaei et al 2003). During cold acclimation, the accumulation of sucrose is related to increases in activities of SPS and SuSy, while sucrose content is negatively regulated by the activity of acid invertase (Gutierrez-Miceli et al 2002;Bhowmik et al 2006). In addition, sugars such as sucrose and glucose may also play a role in regulation of cold-induced expression of genes in plants (Tabaei-Aghdaei et al 2003).…”
mentioning
confidence: 99%
“…The extraction and enzyme assays were done as described by Gutiérrez-Miceli et al (2002). Briefly, SPS and SUSY were extracted, dialyzed, partially purified on a micro-scale ω-aminohexyl-agarose column as described by Dancer et al (1990) and recovered by washing with 500 mM NaCl solution.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Generally, carbon metabolism starts from the breakdown of sucrose during canola seed filling (White et al 2000). Invertase and sucrose synthase (SUS) are two enzymatic systems that catalyze sucrose in consequential metabolism (Schmalstig and Hitz 1987;Gutiérrez-Miceli et al 2002;Fallahi et al 2008). In canola, considerable amounts of hexose accumulate in the early developing silique and seed (mainly in the form of liquid endosperm) (King et al 1997;Hill et al 2003).…”
Section: Introductionmentioning
confidence: 99%